2018
DOI: 10.2147/clep.s154914
|View full text |Cite
|
Sign up to set email alerts
|

The impact of different strategies to handle missing data on both precision and bias in a drug safety study: a multidatabase multinational population-based cohort study

Abstract: BackgroundMissing data are often an issue in electronic medical records (EMRs) research. However, there are many ways that people deal with missing data in drug safety studies.AimTo compare the risk estimates resulting from different strategies for the handling of missing data in the study of venous thromboembolism (VTE) risk associated with antiosteoporotic medications (AOM).MethodsNew users of AOM (alendronic acid, other bisphosphonates, strontium ranelate, selective estrogen receptor modulators, teriparatid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 15 publications
(27 reference statements)
0
19
0
Order By: Relevance
“…[33][34][35][36] In the literature, many statistical analyses and simulation articles have indicated that either multiple imputation techniques or analyses that account for missing data are superior to complete case analyses. [33][34][35][36][37] However, we noticed that such techniques are counterintuitive to many readers. Consequently, we have frequently been asked by journal reviewers to report complete cases, despite literature advising otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36] In the literature, many statistical analyses and simulation articles have indicated that either multiple imputation techniques or analyses that account for missing data are superior to complete case analyses. [33][34][35][36][37] However, we noticed that such techniques are counterintuitive to many readers. Consequently, we have frequently been asked by journal reviewers to report complete cases, despite literature advising otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…In summarizing the use of EHR data to develop risk prediction models, Goldstein et al [ 9 ] found that only 58 of the 90 studies evaluated addressed missing data prior to analysis. The simplest approaches toward managing missing values involve selecting subsets of the data that contain complete information [ 11 , 12 ], and using stratified mean imputation used to fill-in missing values [ 13 ]. Others have designed functions to interpolate longitudinal variables with limited individual-level variability that are typically not dependent on other covariates [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Simpler approaches toward EHR imputation must consider whether missing values are missing completely at random (MCAR), missing at random (MAR), or missing not at random (MNAR) [ 14 ]. Conditional imputation methods may be used to account for these dependencies, most effectively if missing data are MAR [ 10 , 12 , 15 ]. While they may improve completeness and predictive precision, these methods may be computationally intensive when applied to large-scale EHR data with significant amounts of missing values.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 For example, one study showed that risk estimates of venous thromboembolism associated with anti-osteoporotic medications were substantially affected by the use of different strategies for the handling of missing data, leading to differences in the direction of treatment effect estimates. 8 Missing data can arise at several stages within a multi-database pharmacoepidemiologic study. Like in a single database study, data may not be recorded at the stage of data entry into the database.…”
Section: Introductionmentioning
confidence: 99%
“…14 Methods to account for sporadically missing data, such as multiple imputation (MI) and inverse probability weighting, are widely known. 8,15 To handle systematically missing data, a practical approach is to exclude the missing variable from the analyses or exclude an entire database. 8 A recently proposed alternative is multi-level MI (MLMI), which can account for both sporadically and systematically missing data.…”
Section: Introductionmentioning
confidence: 99%